1994
DOI: 10.1128/jb.176.12.3738-3748.1994
|View full text |Cite
|
Sign up to set email alerts
|

Growth phase variation of integration host factor level in Escherichia coli

Abstract: We have measured the intracellular abundance of integration host factor (IHF), a site-specific, heterodimeric DNA-binding protein, in exponential-and stationary-phase cultures of Escherichia coli K-12.Western immunoblot analysis showed that cultures that had been growing exponentially for several generations contained 0.5 to 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
99
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 76 publications
4
99
0
Order By: Relevance
“…Reporter enzyme assays and nested deletion experiments have suggested the presence of an IHF site in the arcA promoter regulatory region and shown that arcA gene expression is elevated more than 3-fold in an IHF Ϫ E. coli strain growing in glucose minimal medium under aerobic conditions. 5 We have identified an IHF-binding site in the arcA promoter regulatory region, and our data show a 3.9-fold increase in arcA mRNA expression in strain IH105 growing under similar conditions. Gunsalus and co-workers (49 -52) also use reporter enzyme assays to examine the expression of several tricarboxylic acid cycle (fumA, gltA, icdA, mdh, mur, and sucA) and respiratory genes (atp, cydA, and cyoA) in IHF ϩ and IHF Ϫ strains.…”
Section: Examples Of Direct Effects Of Ihf On Gene Expression Profilementioning
confidence: 66%
See 1 more Smart Citation
“…Reporter enzyme assays and nested deletion experiments have suggested the presence of an IHF site in the arcA promoter regulatory region and shown that arcA gene expression is elevated more than 3-fold in an IHF Ϫ E. coli strain growing in glucose minimal medium under aerobic conditions. 5 We have identified an IHF-binding site in the arcA promoter regulatory region, and our data show a 3.9-fold increase in arcA mRNA expression in strain IH105 growing under similar conditions. Gunsalus and co-workers (49 -52) also use reporter enzyme assays to examine the expression of several tricarboxylic acid cycle (fumA, gltA, icdA, mdh, mur, and sucA) and respiratory genes (atp, cydA, and cyoA) in IHF ϩ and IHF Ϫ strains.…”
Section: Examples Of Direct Effects Of Ihf On Gene Expression Profilementioning
confidence: 66%
“…They are abundant proteins that bind to many sequence-specific but degenerate DNA sites and affect processes that require DNA duplex destabilization such as DNA replication, recombination, and transcription (5)(6)(7)(8)(9)(10). These proteins also affect the expression of many genes (operons), but unlike the global regulators of the previous class, they do not respond to small molecule metabolic co-regulators and there is no obvious metabolic coherence among the genes whose expression they affect.…”
mentioning
confidence: 99%
“…Antibodies were generated with the following peptide to the C terminus of HU PG0121: ISIPARKVVRFKPGSTLELK by Robert Sargeant (Ramona, CA), as previously described for generating antibodies to histone-like proteins (Ditto et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…In E. coli, the four most abundant nucleoid-associated proteins are factor for inversion stimulation (Fis), histone-like nucleoid structuring protein (H-NS), heat-unstable nucleoid protein (HU) and integration host factor (IHF) [19][20][21][22][23][24][25]. However, at present, a clear picture of how the E. coli nucleoid is organized is far from being complete.…”
mentioning
confidence: 99%